2001
DOI: 10.1093/aje/154.5.466
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reproducibility of a Food Frequency Questionnaire for Pregnant Finnish Women

Abstract: The authors developed a self-administered 181-item food frequency questionnaire (FFQ) to assess dietary intake during pregnancy for Finnish women from August 1995 to July 1996. In the validation study (n = 113), the data that were collected by using two 5-day food records completed during the eighth month of pregnancy were compared with FFQ data. The intake of foods and nutrients was higher as determined by FFQ than that assessed using food records. Pearson correlation coefficients for nutrients, after adjustm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

44
251
14
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(318 citation statements)
references
References 17 publications
44
251
14
9
Order By: Relevance
“…The correlations found between the two dietary methods were within the range observed in other validation studies in pregnant women 37,38 , and lower than those reported in non-pregnant populations 39 -41 . For logistical reasons, the time between the administration of the FFQ and the reference methods was on average 24 days, which meant that 65% of the participants had had weight changes of .…”
Section: Discussionsupporting
confidence: 71%
“…The correlations found between the two dietary methods were within the range observed in other validation studies in pregnant women 37,38 , and lower than those reported in non-pregnant populations 39 -41 . For logistical reasons, the time between the administration of the FFQ and the reference methods was on average 24 days, which meant that 65% of the participants had had weight changes of .…”
Section: Discussionsupporting
confidence: 71%
“…A high proportion of study participants ($70 %) were categorized into the same or adjacent quartiles for estimated energy, carbohydrate, Ca, K, fibre, Zn, cholesterol, vitamin A, riboflavin, niacin, vitamin C, vitamin E and folic acid in both gestational periods. In a study involving Finnish pregnant women, Erkkola et al (15) found estimated nutrient intakes measured by an FFQ to be 30-40 % higher than mean values calculated using food records. According to Robinson et al (11) , higher consumption reported by FFQ may result from the bigger portions used in the FFQ or be due to overreporting of intake frequency.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding the assessment of food consumption, the limited ability of the FFQ to estimate real intake, as characterized in a relative validity study comparing FFQ and 24 h dietary recalls (29) , is another limitation. Furthermore, lactating women may overestimate food consumption (51)(52)(53) . Another limitation is the use of reported, rather than measured, pre-pregnancy weight.…”
Section: Discussionmentioning
confidence: 99%